Herbert Hoover papers - Hoover, Herbert, 1874-1964.
Miscellaneous papers of or relating to Hoover. Includes correspondence with Brand Whitlock, engagement diary, trust deed for land, speech, and other papers.
In part, photocopies.
U.S. president and statesman.
Keywords: Whitlock, Brand, -- 1869-1934 -- Correspondence; Presidents -- United States; Statesmen